The Impact of Household Size on Lexical Typicality: An Early Link Between Language and Social Cognition? - Mayor, Julien; Arias-Trejo, Natalia; Alva, Elda A. (Frontiers in Psychology, 2018)
To communicate successfully, speakers need to use words that are understood by their listeners; they thus need to understand that others have vocabularies different than their own. A key question is whether this social cognition skill is already present in infancy, and whether it can have an impact on early language production. Analysis of the vocabularies of 550 Mexican children revealed that, at 24 months of age, but not at 18 nor at 30 months of age, those who were raised in households with larger numbers of children had more stereotypical vocabularies than those with fewer children. This finding is discussed in light of the hypothesis that communicative pressure may shape early word production; it suggests that bidirectional effects between social cognition and language acquisition are present at two years of age.